Comparative Study of the Vertebral Heart Scale (VHS) and the Cardiothoracic Ratio (CTR) in Healthy Poodle Breed dogs - Azevedo, Gisllyana Medeiros; Pessoa, Gerson Tavares; Moura, Laecio da Silva; Sousa, Francisco das Chagas Araújo; Rodrigues, Renan Paraguassu de Sá; Sanches, Marina Pinto; Fontenele, Rayssa Dourado; Barbosa, Maria Angélica Parentes da Silva; Neves, Willams Costa; Sousa, João Macedo de; et al. (Acta Scientiae Veterinariae, 2016)
Background: Veterinary cardiology has been widely divulged, especially because of the search for diagnostic methods that allow early identification of heart disease in companion animals. Several techniques are available, such as digital radiography (DR), computerized tomography (CT) and magnetic resonance (MR) that are being applied to patients with various diseases. VHS has been widely used in clinical practice in veterinary medicine as a way to diagnose heart size increases in lateral thoracic radiography in small animals. Cardiothoracic ratio (CTR) is a predictive factor for cardiac insufficiency in humans. In veterinary medicine, this index is still little used. The objective of the present study was to compare the vertebral heart scale (VHS) and cardiothoracic ratio (CTR) to assess changes in the size of the cardiac silhouette dogs in thoracic radiographs. Materials, Methods & Results: The VHS and CTR of forty healthy poodle breed dogs (20 males and 20 females) from University Veterinary Hospital at the Federal University of Piauí were assessed. The animals were placed in supine and lateral decubitus, to obtain radiographic images in dorsoventral (DV) and right and left laterolateral projections of the thoracic region. The images acquired on the photosensitive radiographic chassis were analyzed by digital radiographic image system installed in the Image Diagnosis Service of the University Veterinary Hospital -HVU/UFPI. VHS (Vertebral Heart Scale) measurements were taken using the sum of the heart length and heart width at its greatest diameter, comparing with the vertebral bodies from the fourth thoracic vertebra (T4). The CTR was assessed by comparing the greatest width of the heart silhouette and the distance between the thoracic walls at height T8. The heart width was measured from the two greatest distances (ML and MR), from the vertical line that divides the limit between the right and left sides of the heart, at the point of its greatest diameter. Similarly, the thoracic width was measured at the point of greatest thoracic diameter (MTD). The mean of the VHS and CTR in the males was 9.83 ± 0.85v and 0.48 ± 0.05, respectively. The females showed values of 9.65 ± 0.65v and 0.50 ± 0.03, respectively (P > 0.05). The mean of the VHS and CTR, considering males and females, was 9.72 ± 0.73v and 0.48 ± 0.04, respectively. VHS and weight correlated positively (r = 0.96), as the CTR and weight (r = 0.94). VHS and age showed high correlation (r = 0.96) as CTR and age (r = 0.93). VHS and CTR showed high correlation (r = 0.96). Discussion: Although congenital malformations and genetic diseases can occur, the acquired heart diseases correspond to most of the complications found in dogs. VHS increases considerably 6 to 12 months before the development of congestive heart failure (CHF). The poodles studied, considering the universe of males and females (P < 0.05), presented mean VHS values of 9.72 ± 0.73v. Similarly, there was no significant difference between genders for VHS measured in right and left decubitus in normal dogs. The cardiothoracic ratio measured for the poodles studied showed mean values of 0.48 ± 0.05. In humans, values below 0.5 are considered normal, while values above this may indicate the presence of cardiomegaly. The CTR is intimately related to the volume of the left ventricle and CTR values above 0.5 in humans are pathological. Our results demonstrated that VHS and CTR showed strong correlation in their measurements, suggesting that CTR, constantly used in humans, could be considered as a tool to assess the size of the heart silhouette in dogs of the poodle breed.